Methodology of AA CRASH: a prospective observational study evaluating the incidence and pathogenesis of adverse post-traumatic sequelae in African-Americans experiencing motor vehicle collision. Issue 9 (6th September 2016) - Linnstaedt, Sarah D; Hu, JunMei; Liu, Andrea Y; Soward, April C; Bollen, Kenneth A; Wang, Henry E; Hendry, Phyllis L; Zimny, Erin; Lewandowski, Christopher; Velilla, Marc-Anthony; Damiron, Kathia; Pearson, Claire; et al.
Abstract : Introduction: A motor vehicle collision (MVC) is one of the most common life-threatening events experienced by individuals living in the USA. While most individuals recover following MVC, a significant proportion of individuals develop adverse post-traumatic sequelae such as post-traumatic stress disorder or persistent musculoskeletal pain. Adverse post-traumatic sequelae are common, morbid and costly public health problems in the USA and other industrialised countries. The pathogenesis of these disorders following MVC remains poorly understood. In the USA, available data suggest that African-Americans experience an increased burden of adverse post-traumatic sequelae after MVC compared to European Americans, but to date no studies examining the pathogenesis of these disorders among African-Americans experiencing MVC have been performed. Methods and analysis: The African-American CRASH (AA CRASH) study is an NIH-funded, multicentre, prospective study that enrols African-Americans (n=900) who present to the emergency department (ED) within 24 hours of MVC. Participants are enrolled at 13 ED sites in the USA. Individuals who are admitted to the hospital or who report a fracture or tissue injury are excluded. Participants complete a detailed ED interview that includes an assessment of crash history, current post-traumatic symptoms and health status prior to the MVC. Blood samples are also collected in the ED using PAXgene DNA and PAXgene RNA tubes. Serial mixed-mode assessments 6 weeks, 6 months and 1 year after MVC include an assessment of adverse sequelae, general health status and health service utilisation. The results from this study will provide insights into the incidence and pathogenesis of persistent pain and other post-traumatic sequelae in African-Americans experiencing MVC. Ethics and dissemination: AA CRASH has ethics approval in the USA, and the results will be published in a peer-reviewed journal.